Globalization in everyday life of Iranian high-school students - Pasha, Nourollah (2014)
This research attempts to explore the Iranian high school students' point of view about globalization and to explain influence of globalization in their daily life, and to interpret implications of alternation among the students. Indeed, knowing and exploring the challenges of students' everyday life in light of globalization is my academic interest as a teacher who works with the students about two decades. This research has conducted a qualitative method to collect data from the high school students in Tehran, capital of Iran. A total of 31 in-depth interviews are the sources of information. The facts were gathered and presented qualitatively, illustrating globalization in the daily life of Tehranian high school students based on the research questions. The findings show that the students perceive globalization in different ways and derive different meanings from it. They perceive globalization as development, open relationship, dissemination of a massive amount of information around the world, and also suppression and exploitation of developing countries by the West. The findings indicate that globalization has influenced the Tehranian high school students' daily life within two dimensions, namely, de-territorialization and pluralism. In fact, globalization has influenced the students' eating and clothing habits, their communication and concerning distant events as well as their perception about other cultures and religions. Their everyday life has been increasingly defined as a global level with global standards. Globalization in the students' everyday life has given birth to two types of students: globalized students and alternated students. Globalized students are those who mostly wear branded clothes, eat their meals in fast food restaurants, communicate with others, and using modern media. They are concerned about distant events, and have plural and tolerant perception about other cultures and religions. Alternated students are globalized students who have negative perceptions about their culture and being Iranian.